Fostering Sustainabel Livelihood of the Saga Indigenous Community through Conservation Partnership in Kelimutu National Park, Nusa Tenggara Timur - Avila Delvion, Bertila; Permadi, Dwiko Budi; Marhaento, Hero (Jurnal Wasian, 2023)
Currently, the Kelimutu National Park (KNP) is developing a conservation partnership approach to improve the welfare of local communities while restoring degraded ecosystems. This approach provides access to the community so that it is expected to be able to increase participation and be able to live harmoniously with the KNP environment. Communities around KNP still depend on forests and forest land to find a source of livelihood. Also, partnership schemes can be a solution to overcome tenurial conflicts. This study aims to describe the efforts of conservation partnerships in increasing sustainable livelihood assets , including natural, human, physical, social and financial capital, so that they can be used to measure the success of implementing conservation partnerships. This study uses qualitative methods with in-depth interviews and observation as data collection techniques. The results show conservation partnership in KNP increases natural capital as KNP establishes traditional zones for traditional coffee agroforestry practices, human capital through eco-interpreter training, social capital by strengthening Saga indigenous groups, and financial capital which indirectly increases accessibility and infrastructure needed for rural development. economy and tourism. Nonetheless, further efforts are still needed to increase the effectiveness and success of this conservation partnership program.